Estimation of the resonance frequency of rotational and translational signals evoked by mining-induced seismicity - Nawrocki, Dariusz; Mendecki, Maciej J.; Teper, Leslaw (Frontiers in Earth Science, 2024)
The article presents horizontal-to-vertical (H/V) spectral ratios calculated for rotational and translational signals, which were registered by four independent seismic stations. H/V curves were estimated using the Fourier Spectrum Analysis (FSA) and the Response Spectrum Analysis (RSA). The standard approach of H/V determination using the FSA may lead to problems with accurate resonant frequency determination due to evident multi-amplification peaks occurrence on the spectrum. In contrast, only a general amplification peak is expected in the case of the RSA. The studies show that in the case of translational motion, the H/V estimations using the RSA derived clear information of the resonant frequency peak, confirming the method's usefulness in the case of multiamplification peaks. The opposite situation was noticed in the case of the rotational motion. The derived H/V spectrum, using the RSA, produced single amplification peaks for the seismic stations, where the sensors were mounted on a small floor at a significant distance from the walls. In cases where the sensors were deployed on the building floor, a decrease in the reliability of the RSA method was noticed. Separate analysis confirmed that in the case of the translations, the response and Fourier spectrum were close at low frequencies, which was not observed for the rotational motion. The results of the studies suggested that the possibility of the estimations of the H/V spectrum using the RSA algorithm is strongly limited for rotational motions due to the size of the floor and distance to the building walls, where the sensors were mounted.